Turkey, Israel, Greece: Reshuffling in the Eastern Mediterranean. - Ioannis Mazis (Civitas Gentium, 2018)
Lots have happened in the East-Mediterranean since the beginning of the third millennium. A list of the main events reveals a long series of issues that took place in the region and heavily affect it.  The impact of these issues and events will stay with us for the foreseeable future and is heavily discernible in the relations between the eastern- Mediterranean non- Arab littoral countries: Turkey, Israel, Greece and Cyprus. This list includes, for example, the 2000s deteriorating relations between Turkey and Israel (in 2016 the two resumed full diplomatic relations); the current crises in the relations between Turkey several Middle Eastern countries (Egypt, Syria, Iraq); the civil war that rages in Syria since 2011 and Turkey’s deep involvement in it; acts of Islamist led terrorism, attacks by ISIS1, and manifestations of religious extremism that heavily affect daily life, economies and tourism in Turkey, Egypt, Jordan, Iraq, as well as in other places; illegal immigrants, refugees and asylum seekers that inundate Turkey, Greece (and via them) many EU countries; energy explorations in the Mediterranean Sea; issues related to civil rights, minorities, the growing tendencies towards strong executives and authoritarian regimes at the expense of democracy and pluralism; heavy internal changes like the decline of Turkish Kemalism, the growing impact of religion in Israel and Turkey, and the ﬁ nancial crisis of Greece; In addition, the struggle for self-determination of various ethnic groups and peoples (the Kurds, the Palestinians, and others); the Russian reappearance, American disappearance and the EU weak impact on events in the Middle East and the Eastern – Mediterranean - - these and subjects have brought about dramatic changes in the Eastern Mediterranean sub-system. 1. See at the end of this text: ANNEX: Evidence on the Collaboration of Turkey with ISIS and other jihadist groups, as well as relevant testimonies from international sources. From the Turkish standpoint, the events in our region express what is happening in the global arena: Europe is aging, its economy and currency are limping and convulsing, and the EU radiates political disintegration (the Brexit) and economic weaknesses. The US is suffering from an economic crisis, it is globally and politically on the decline, internally it is also on the decline following the eight years’ presidency of Barak Obama, and the November 2016 election of President Donald Trump. Simultaneously, other powers (China, Russia) strive to replace American hegemony all around the globe. Also from the standpoint of Ankara, Turkey desires to be now a rising «uneasy» power, and is demarcating the limits of its inﬂ uence: Central Asia, the Caucasus and the Balkans, on the one hand; black Africa, North Africa, and the Middle East, on the other. Following several setbacks, Turkish- Russian relations are developing and disagreements have been settled. And all these developments and events have greatly affected the three eastern - Mediterranean non - Muslim countries (Greece, Israel, Cyprus), and the region’s sole non- Arab but Muslim country- Turkey. In our paper we will make an attempt to describe and analyze the major impacts that these events and issues have had on the developments in the eastern- Mediterranean, with particular focus on Turkey and Israel, and the growing cooperation between Greece and Israel.